Report of the Working Group on Development of Human Resources for Health for the Tenth Five Year Plan (2002-2007) - Planning Commission (Planning Commission, 2001)
The Working Group Report on Development of Human Resources for Health (2001) evaluates India’s healthcare workforce, highlighting critical shortages, especially in rural areas, and regional imbalances in medical education. With 181 medical colleges producing 17,000 graduates annually, disparities persist, and specialist availability remains limited. The report recommends creating a centralized data bank, implementing a five-year re-registration linked to Continuing Medical Education (CME), expanding medical colleges in underserved regions, and increasing postgraduate seats in key specialties. It also emphasizes standardizing medical education through Universities of Health Sciences and enhancing workforce skills via CME and paramedical training. The recommendations aim to strengthen equitable distribution, improve quality, and ensure an effective healthcare system accessible across India.
Government of India Planning Commission October 2001
Government of India Planning Commission October 2001
Keywords: Human Resources; Health Workforce; Medical Education; Rural Healthcare; Specialist Shortage; Continuing Medical Education; Data Bank; Medical Colleges; Health Policy; Workforce Distribution